Mediated discourse analysis : negotiating metrosexuality within L’oréal Men Expert’s packaging discourse / Cheong Huey Fen - Cheong, Huey Fen (2014)
Gender, the social rules and standards of behaviours imposed on male and female, has been a popular social debate. The modern pursuit of body beautiful and fashion among metrosexuals that trespasses feminine space causes uncertain social acceptance. Hence, the study aims to explore the marketing strategies in the grooming industry to overcome this uncertainty. Choosing the giant beauty producer, L’Oréal, the case study investigates its success story in cross-gender brand extension to L’Oréal Men Expert (LME), while continues to thrive in both female and male markets. Using Scollon's (2001, 2004) Mediated Discourse Analysis, the qualitative research aims to analyze how metrosexuality is negotiated through social interactions within the packaging discourse of L’Oréal Men Expert (LME), in comparison to L’Oréal Paris (LP). Approaching through actions, the study analyses how each social action within the packaging discourse is mediated by multimodal features strategized by gendered practices. Incorporated along are elements from structural semiotics, i.e. Barthesian Order of Signification and paradigmatic analysis, as well as Difference Framework from language and gender. The latter aims to depict the interaction (or tension) between traditional gender dichotomy (which causes gender stereotyping) and contemporary gender diversity (referring to queer identities, e.g. metrosexuality) that give rise to social controversies pertaining to metrosexuality. The ultimate aim is to uncover the marketers' manipulating (negotiating) strategies in overcoming traditional gender dichotomy to accept contemporary gender diversity. Narrowing the scope to whitening products, the analysis on a total of twelve (12) product packaging (consisting cleansers, toners and moisturizers) reveals different conceptual emphasis between male and female products. In LP/White Perfect, luxury, aesthetic, sensuality, vanity, attractiveness (beauty), passivity, femininity and skin-whitening are emphasised, while expertise, problems, functionality/performance, manual, unattractiveness, activeness, masculinity/anti-femininity and skin-brightening in LME/White Activ. These propose two different sets of gendered concepts in beauty and grooming contexts, separating metrosexuality from femininity. The study also depicts the strategies of negotiating metrosexuality in LME through both gender dichotomy and gender diversity, using binary/digital oppositions (either/or) and/or analogue oppositions (more/less) of both signifiers (multimodal features) and signifieds (meaning). Negotiation through gender dichotomy includes: 1) construct masculinity (claim masculinity); 2) avoid femininity (deny femininity); and 3) juxtapose masculinity and femininity (challenge femininity). On the contrary, negotiation through gender diversity is conducted through three ways: 1) downplay femininity (reduce femininity); 2) overshadow femininity (highlight masculinity); and 3) compromise femininity (add autonomy in femininity/add femininity in masculinity). Another significant discovery is the different portrayal between LP and LME for the same concepts. This includes portraying LP as a luxury worth-spending, aligns with the slogan "Because you're/I'm worth it", whereas LME sells the concept of cheap but highly functional products that are worth-buying "because it's worth it". Last but not least, the study uncovers the complementary nature between linguistics and marketing and further proposes the potential collaboration between both realms that serve as 'heuristic/explanation tool' and 'verification tool' respectively. In other words, it proposes the collaboration between the "grammar" and "dictionary" of semiotics. (Keywords: metrosexuality, masculinity, gender stereotyping, product packaging, mediated discourse analysis, Difference Framework, paradigmatic analysis, Barthesian Order of Signification)